2013
DOI: 10.1017/s1041610213002044
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of and attitudes towards Alzheimer's disease screening in elderly German adults

Abstract: This study suggests that acceptance can reliably be assessed with the section "Acceptance of Alzheimer's disease screenings" of the German PRISM-PC questionnaire. Furthermore, the majority of elderly German adults would like to be screened for Alzheimer's disease regularly, which might be an effective starting point in order to implement routine dementia screenings. As the sample is a convenience sample of (relatively) healthy older adults, generalizability of these results is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 21 publications
4
32
0
Order By: Relevance
“…They have less prejudice and are more likely to correctly recognize some abnormal behaviors or behaviors of dementia. They tend to be less skeptical about early detection of dementia and want to be screened for AD even on a regular basis [68]. Simultaneously, we should also be vigilant about the correctness of AD information, because non-professional information is more likely to bring fear of AD [26].…”
Section: Discussionmentioning
confidence: 99%
“…They have less prejudice and are more likely to correctly recognize some abnormal behaviors or behaviors of dementia. They tend to be less skeptical about early detection of dementia and want to be screened for AD even on a regular basis [68]. Simultaneously, we should also be vigilant about the correctness of AD information, because non-professional information is more likely to bring fear of AD [26].…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high PPV of the GPCOG in our “passive case‐finding” population makes it an appropriate cognitive assessment tool to improve the case‐finding approach in a general practice setting, and to determine whether further investigations or referrals are warranted. A short questionnaire to screen for dementia is theoretically acceptable to most patients (Braun et al, ; Magin et al ., ), and the GPCOG was well accepted by both GPs and patients as a suitable tool for checking memory in this study. Modifications and refinements to the case‐finding approach and/or tools used should pay particular attention to younger and less impaired patients, as they are more likely to receive a false negative result.…”
Section: Discussionmentioning
confidence: 99%
“…However, many doctors are uncomfortable when giving the diagnosis of dementia. The reasons for this difficulty may include doubt that the patient, and his/her family, would understand the disease, fear of prejudice in accepting the disease, personal uncertainties about the diagnosis, and the hesitation to raise hopelessness in the patient (41). Although patients in Western societies usually prefer to know about their diagnoses, doctors and patients' families choose to not give information to their patients about the diagnosis.…”
mentioning
confidence: 99%
“…Although patients in Western societies usually prefer to know about their diagnoses, doctors and patients' families choose to not give information to their patients about the diagnosis. In fact, studies have shown that only about a half of the patients are aware of their diagnoses (41).…”
mentioning
confidence: 99%